Compositions of professionalism in counselling work: An embodied and embedded intersectionality framework. (December 2016) - Adamson, Maria; Johansson, Marjana
This article explores the embodied compositions of professionalism in the context of the counselling psychology profession in Russia. Specifically, we develop an embodied intersectionality framework for theorizing compositions of professionalism, which allows us to explain how multiple embodied categories of difference intersect and are relationally co-constitutive in producing credible professionals, and, importantly, how these intersections are contingent on intercorporeal encounters that take place in localized professional settings. Our exploration of how professionalism and professional credibility are established in Russian counselling shows that, rather than assuming that a hegemonic 'ideal body' is given preference in a professional context, different embodied compositions may be deemed credible in various work settings within the same profession. An embodied intersectionality framework allows us to challenge the notion of a single professional ideal and offer a dynamic and contextually situated analysis of the lived experiences of professional privilege and disadvantage.